Systematization and accounting of buildings and structures - Jurakulov Doniyor Ochilovich; Ibragimov Lazizbek Toshpulat o’g’li; Akhmedova Madina G’ayrat qizi; Hazratov Shaxzod Sunnatillo o’g’li (Research Parks Publishers, 2021)
This article describes the important tasks of summarizing and systematizing cadastral data on buildings and structures in each region as of each quarter and 31 December, as well as maintaining a general account (balance) for the region